Pindar's Pythian Twelve: A Linguistic Commentary and a Comparative Study / - Massetti, Laura (Brill, 2024)
Pindar's Pythian Twelve is the only choral lyric epinicion in our possession composed for the winner of a non-athletic competition. Often regarded as an ode of straightforward interpretation, close analysis of the text reveals that it presents several challenges to modern readers. This book offers an updated translation of the text and an investigation of the main interpretative issues of the epinicion with the aid of historical linguistics. By identifying devices which Pindar might have inherited from earlier periods of poetic language, the study provides insights into the thematic aspects of the ode as well as on Pindar's compositional technique.
10.1163/9789004694132
Keywords: Pindar; Pindar.; Pythian odes.